Metabolic disorders and their impact on retinal blood flow in patients with age-related macular degeneration and diabetes mellitus: data from optical coherence tomography angiography - N. S. Lutsenko; T. S. Kyrylova (Zaporožskij Medicinskij Žurnal)
Aim – to examine the impact of metabolic disorders on retinal blood flow in patients with age-related macular degeneration (AMD) and diabetes mellitus using optical coherence tomography angiography (OCT-A).